폐색전증에서 나선형 컴퓨터 전산화 단층촬영의 관찰자간의 일치도에 관한 연구 - 김양기; Yang Ki Kim; 이영목; Young Mok Lee; 김기업; Ki Up Kim; 어수택; Soo Taek Uh; 김용훈; Yong Hoon Kim; 박춘식; Choon Sik Park; et al. (Tuberculosis and respiratory diseases, 2005)
Background : A pulmonary embolism often presents with nonspecific symptoms and signs. However, a delayed diagnosis can result in catastrophic outcome. The majority of preventable deaths associated with a pulmonary embolism can be ascribed to a missed diagnosis rather than to the failure of existing treatments. Therefore, accurate and rapid diagnostic methods are essential for the management of a pulmonary embolism. The recent generation of multidetector-row spiral CT scanners appears to outperform other imaging modalities in detecting a central and peripheral pulmonary embolism. However, there are some variations in the interpretations of the findings between observers. This study examined the inter-observer differences of the diagnoses in patients with a pulmonary embolism. Method : 64 patients who were diagnosed with a pulmonary embolism either clinically or with spiral chest CT from 2002 to 2004, were included. Two thoracic radiologists interpreted the multidetector-row spiral CT in terms of the diagnosis of a pulmonary embolism and the location of the thrombus independently. Among 64 patients, 14 patients were excluded because there was no evidence of a pulmonary embolism or there was different interpretation of the pulmonary embolism between radiologists. A clinical diagnosis was based on "Rules for predicting the probability of embolism". Results : The mean score of the patients according to the Wells method was $3.91{±}0.30$ (0-9). The accordance of the radiologists was 95% in the main, 85% in the lobar, 91.2% in the segmental, and 96% in the sub-segmental pulmonary arteries. After excluding the negative interpretation from both radiologists, their agreement was 76.2%(${κ}.$ 0.83) in the main, 57.6%(${κ}.$ 0.63) in the lobar, 51.5%(${κ}.$ 0.63) in the segmental, and 34.6%(${κ}.$ 0.49) in the sub-segmental pulmonary arteries. Conclusion : Chest CT has been recently applied to patients suspected of having a pulmonary embolism. It was found that spiral CT is a rapid test for diagnosing a thrombus, and there was reliable accordance between the observers from the area of the large pulmonary arteries. However, there was a lack of agreement between the observers in diagnosing thrombi located distal to the sub-segmental arteries. 연구배경 : 폐색전증은 비특이적인 증상과 징후로 인해 진단이 지연될 수 있고 이로 인해 치명적인 결과를 가져 올 수 있으나 정확한 진단과 적절한 치료를 시행하는 경우 재발 및 사망의 경우가 흔치 않다. 폐색전증과 관련되어 나타나는 예방 가능한 사망의 대부분은 치료실패 보다는 진단이 지연되는 경우에서 기인하므로 보다 정확하고 빠른 검사법을 요구하게 되었다. 나선형 흉부 전산화 단층촬영은 혈전을 직접 관찰할 수 있고 이외의 부가적 진단이 가능하며 최근 multidetector-row spiral CT의 도입으로 중심 및 말초의 혈전도 더 정확한 진단이 가능해져 나선형 흉부 전산화 단층촬영술이 진단에 어느 정도의 신뢰성을 보이는지 비교, 연구하였다. 방 법 : 2002년 9월부터 2004년 9월까지 임상적 소견 및 나선형 흉부 전산화 단층촬영을 통해 폐색전증을 의심하거나 진단하였던 환자 64명을 대상으로 하였다. 진단시의 임상적 소견은 Wells 등의 "Rules for predicting the probability of embolism"을 기준으로 하여 평가하였다. 진단 당시 시행한 나선형 흉부 전산화 단층촬영 소견은 2명의 흉부 방사선과 의사가 독립적이고 맹검의 방식으로 각 병변의 해부학적 위치 및 진단적 근거에 대해 재판독을 시행하였다. 결 과 : 임상적 가능성에 대한 총 점수의 평균값은 $3.91{±}0.30$ (0-9)였고 저확률군은 9례, 중등도 확률군은 36례, 고확률군은 5례 였다. 관찰자간의 일치율은 주폐동맥에서 95.0%, 엽폐동맥에서 85.0%, 분절 폐동맥에서 91.2% 및 아분절 폐동맥에서 96.0%를 보였다. 두 관찰자 모두에서 음성소견을 보인 분지를 제외한 후의 일치율은 주폐동맥에서 76.2% (kappa 0.83), 엽폐동맥에서 57.6% (kappa 0.63), 분절 폐동맥에서 51.5% (kappa 0.63) 및 아분절 폐동맥에서 34.6% (kappa 0.49)를 보였다. 결 론 : 폐색전증이 의심되는 경우 진단에 일차적으로 이용되고 있는 나선형 흉부 전산화 단층촬영은 주폐동맥, 엽폐동맥 및 분절 폐동맥에서 관찰자간의 일치율이 높아 신뢰할 수 있는 검사법으로 비교적 신속하고 정확하나 아분절 폐동맥 이하의 작은 폐동맥은 진단적 오차가 커질 수 있다.